A Estimation of Blue Carbon (Bc) Post-Development of Mandeh Regions - Angraina, Dilla; Rahmi, Lailatur (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
The Mandeh regions is one of the coastal and marine ecosystems in the Province of WestSumetera. Mandeh regions has mangrove forests, seagrass beds and sizable coral reefs. Nowadays, Mandehregions has been completed in the development, especially in development of road access to increase theacceleration of the development of Mandeh tourist destinations as a new destination in West Sumatra.However, in that development, it turns out that it has affected many forest ecosystems and coastal and marineecosystems, one of which is the reduction of blue carbon which is one of the ways to mitigate climate change.Therefore, this research is very important to do considering the impact of development on the coastal andmarine ecosystems. This research is the first study conducted in the Mandeh regions with a focus on estimatingblue carbon stored in mangrove forests and coral reefs. This study aims to determine and analyze the bluecarbon contained in the Mandeh regions after the development, especially the opening of roads. The resultsshowed that from 1999 to 2019 there was an ecosystems degradation which caused a decrease in carbon stocks.Estimated carbon stock in the mangrove ecosystem is around 257 Mg.C / Ha and coral reefs 3291 g.C / m2.Estimated carbon stock is not much different from other studies in Indonesia, thus after the opening of the roadin Mandeh regions does not significantly affect mangrove ecosystems and coral reefs, so that ocean carbonuptake, is still quite large.